Comparisons of I- and Cl- concentrations on the corrosion behavior of TA4 titanium alloy in azeotropic acetic acid solutions. Issue 1 (1st November 2022) - Deng, Cong; Zhao, Zhongxun; Hu, Huasheng; Li, Xufeng; Luo, Weijian
Abstract : The corrosion problems of TA4 titanium alloy trays were urgent to be solved in the safe and steady production process of the acetic acid distillation column. According to the real corrosion environment of the distillation column, the corrosion behavior of TA4 titanium alloy in simulated azeotropic acetic acid solutions with a series of I - and Cl - concentrations was investigated by electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization measurements. The experimental results showed that the TA4 titanium alloy was much easier to be corrosive with I - and Cl - in the test solution, the passive film resistance R f, the charge transfer resistance R ct, and Warburg impedance W decreased obviously with the increasing concentration of I - and Cl - . The corrosion rate of Cl - was 1.79 times higher than I - on average when the I - and Cl - concentration increased from 0.1 wt.% to 5 wt.%. The inhibition of passive film formation on the surface of TA4 titanium alloy by Cl - is stronger than that of I - .